Reducing Moisture Absorption in Polypropylene Nanocomposites for Automotive Headlamps Using Hydrophobicity-Modified Graphene/Montmorillonite - Pyoung-Chan Lee; Dongwoo Kang; Ji Taek Oh; Jae Young Seo; Donghyeok Shin; Jae-Uk Jung; Youn Ki Ko; Jin Uk Ha; Myeong-Gi Kim (Nanomaterials, 2023)
Polypropylene (PP) is used as a housing material in automotive headlamps but can cause fogging as a result of absorbed moisture and temperature differences between the exterior and interior of the housing. In this study, PP was combined with a graphene/montmorillonite hybrid (MMT-G) to yield a nanocomposite with reduced moisture absorption. Crucially, the modified nanofiller had low hydrophilicity and good compatibility with the PP matrix. Notably, the water contact angle of the MMT-G improved by 676%. Furthermore, the maximum moisture absorption of the PP/MMT-G nanocomposites was reduced by up to 11.22% compared to that of commercial PP composites, and the weight of the headlamp housing was decreased by 3.6%. Therefore, the designed nanocomposites are expected to help mitigate headlamp fogging while slightly reducing the housing weight.